Investigation the Effectiveness of Schema-Based Parenting on Emotion Regulation and Stress in Mothers of Children Under 6 Years Old - karimnejad Isfahani, Reyhaneh; Ansari Shahidi, Mojtaba; Dehghani, Akram (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to examine the effectiveness of schema-based parenting training on emotion regulation and stress in mothers with children under the age of six. Methods and Materials: This research employed a quantitative method with a pre-test, post-test, and follow-up design, involving two experimental groups and one control group. The statistical population included all mothers with children under six years old in the city of Isfahan. Sampling was done purposefully by visiting kindergartens in Isfahan. Based on the cut-off points of the questionnaires and the inclusion and exclusion criteria, 30 participants were selected and randomly assigned into two groups: one experimental group (15 participants) and one control group (15 participants). Schema-based parenting training sessions (competent parenting) based on the protocol by Mehrabian et al. (2022) were conducted for the experimental group, while the control group did not receive any intervention. The research tools included the Abidin Parental Stress Index (1995) - Short Form, and the Shields and Cicchetti Emotion Regulation Checklist (1995). The collected data were analyzed using appropriate statistical tests (Repeated Measures Analysis of Variance and Bonferroni post hoc test) with SPSS software. Findings: Given that the calculated F values for between-group effects (group membership effect) and within-group effects (time effect), as well as the interaction effect of group and time, were significant at the 99% confidence level (P < 0.01), these results indicate a significant difference between the two groups. Furthermore, it suggests that this significant difference exists in at least one of the intervention periods among the research groups. The results of the Bonferroni post hoc test showed a significant difference in the scores of adaptive emotion regulation, instability/negativity, and stress across the research stages between the experimental and control groups (P < 0.01). In other words, schema-based parenting training had a significant positive impact on the research variables (P < 0.01). Conclusion: These results confirm that this approach can be utilized as an effective strategy in improving parenting abilities and reducing psychological challenges in mothers during the parenting period.